Las microalgas como indicadoras de contaminación del sitio La Peaña en las aguas del Río Jubones en el cantón Pasaje - Ponce Castro, Lecy F. (2005)
The resource more important hydric for our country is the river Jerkins, since of him she/he takes the water for the watering of the banana tree plantations and of short cycle, and equally is waters are used in industries and it stops human consumption.